Capillary microsampling in nonclinical safety assessment: practical sampling and bioanalysis from a CRO perspective. (May 2017) - Coleman, David; Smith, Graeme; Lawrence, Rachel; McManus, Deborah; Diaram, Sunetha; Edwards, Joanna
Microsampling has the 3R benefits of refining blood collection techniques while reducing the number of animals required for rodent safety assessment studies. There are significant scientific benefits of correlating study findings with systemic exposure and consequently, there is an industry drive to utilize microsampling in regulatory toxicology studies. This article will focus on capillary microsampling and will discuss the initial considerations before using capillary microsampling, study design and some practicalities of sample collection. From a bioanalytical perspective, the impact of different sample collection and storage workflows on the design of method validation experiments, the suitability of using microsampling for unstable analytes and aspects supporting analysis of peptides, large molecules and for biomarker applications will be discussed.